A Systematic Review of Economic Evaluations of Chemoprophylaxis for Tuberculosis - Shraddha Chavan; David Newlands; Cairns Smith (Journal of Tropical Medicine)
Since treatment of active disease remains the priority for tuberculosis control, donors and governments need to be convinced that investing resources in chemoprophylaxis provides health benefits and is good value for money. The limited evidence of cost effectiveness has often been presented in a fragmentary and inconsistent fashion. Objective. This review is aimed at critically reviewing the evidence of cost effectiveness of chemoprophylaxis against tuberculosis, identifying the important knowledge gaps and the current issues which confront policy makers. Methods. A systematic search on economic evaluations for chemoprophylaxis against tuberculosis was carried out, and the selected studies were checked for quality assessment against a standard checklist. Results. The review provides evidence of the cost effectiveness of chemoprophylaxis for all age groups which suggests that current policy should be amended to include a focus on older adults. Seven of the eight selected studies were undertaken wholly in high income countries but there are considerable doubts about the transferability of the findings of the selected studies to low and middle income countries which have the greatest incidence of latent tuberculosis infection. Conclusion. There is a pressing need to expand the evidence base to low and middle income countries where the vast majority of sufferers from tuberculosis live.